Analisis Perbandingan Profitabilitas Pada Perusahaan Antara Sebelum Dan Sesudah Merger Dan Akuisisi (Studi Kasus Pada Perusahaan Yang Melakukan Merger Dan Akuisisi Di Tahun 2018) - Izzakah, Ita; Sudarsono, Bambang (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
This study aims to find out whether or not there is a difference between before and after mergers and acquisitions in the profitability of companies that carried out mergers and acquisitions in 2018 which were listed on the Indonesia Stock Exchange (IDX). The population used in this study were companies that carried out mergers and acquisitions in 2018 with a total of 74 companies taking samples using the purposive sampling method and 8 companies were selected as samples in the study. The sample which consists of 8 companies are companies that carried out mergers and acquisitions in 2018 which were listed on the Indonesia Stock Exchange. The analytical method used in this study is to use a paired sample t test with the calculation of profitability using the ratio of ROE and NPM. The paired sample t test is a testing technique to be able to find out about the difference between before and after being given treatment on a variable. The results of this study indicate that there is no difference in the profitability of companies listed on the IDX that carried out mergers and acquisitions in 2018. This is shown by using the paired sample t test to obtain an ROE ratio value with a tcount of 1,617 with a significance of 0.127, from the results it can be seen that the significance value is greater than 0.05. Meanwhile, if seen using the NPM ratio value, the t-count value is -0.555 with a significance of 0.587, from these results it can also be seen that the significance value is greater than 0.05. So it can be concluded that there is no difference in company profitability as measured by the ROE ratio and NPM ratio for companies that carried out mergers and acquisitions in 2018 which were listed on the Indonesia Stock Exchange. Keywords: Mergers and Acquisitions, Profitability